Mortality of patients with ST-segment-elevation myocardial infarction without standard modifiable risk factors among patients without known coronary artery disease: Age-stratified and sex-related analysis from nationwide readmissions database 2010-2014 - Sun-Joo Jang; Luke K. Kim; Navjot Kaur Sobti; Ilhwan Yeo; Jim W. Cheung; Dmitriy N. Feldman; Nivee P. Amin; David L. Narotsky; Parag Goyal; S. Andrew McCullough; Udhay Krishnan; Stuart Zarich; et al. (Elsevier, 2023)
Objective: The proportion of ST-segment elevation myocardial infarction (STEMI) patients without standard modifiable risk factors (SMuRFs: hypertension, diabetes, hypercholesterolemia and smoking) has increased over time. The absence of SMuRFs is known to be associated with worse outcomes, but its association with age and sex is uncertain. We sought to evaluate the association between age and sex with the outcomes of post-STEMI patients without SMuRFs among patients without preexisting coronary artery disease. Methods: Patients who underwent primary PCI for STEMI were identified from the Nationwide Readmission Database of the United States. Clinical characteristics, in-hospital, and 30-day outcomes in patients with or without SMuRFs were compared in men versus women and stratified into five age groups. Results: Between January 2010 and November 2014, of 474,234 patients who underwent primary PCI for STEMI, 52,242 (11.0%) patients did not have SMuRFs. Patients without SMuRFs had higher in-hospital mortality rates than those with SMuRFs. Among those without SMuRFs, the in-hospital mortality rate was significantly higher in women than men (10.6% vs 7.3%, p<0.001), particularly in older age groups. The absence of SMuRFs was associated with higher 30-day readmission-related mortality rates (0.5% vs 0.3% with SMuRFs, p<0.001). Among patients without SMuRFs, women had a higher 30-day readmission-related mortality rates than men (0.6% vs 0.4%, p<0.001). After multivariable adjustment, the increased rates of in-hospital (odds ratio 1.89 (95% CI 1.72 to 2.07) and 30-day readmission-related mortality (hazard ratio 1.30 (95% CI 1.01 to 1.67)) in patients without SMuRFs remained significant. Conclusions: STEMI patients without SMuRFs have a significantly higher risk of in-hospital and 30-day mortality than those with SMuRFs. Women and older patients without SMuRFs experienced significantly higher in-hospital and 30-day readmission-related mortality.